Respostas
respondido por:
1
Olá
Vamos lá,
={(-2)²+[(-2)²-3+(-3).√49]:[√256:(-4)] }:(-3)
={ 4+[ 4-3+(-3).7]:[16:-4] }:-3
={ 4+[ 4-3 -21]:[-4] }:-3
={ 4+[ 1 -21]: -4 }:-3
={ 4+[ -20]: -4 }:-3
={ 4 -20: -4 }:-3
={ 4 + 5 }:-3
= 9 : -3
= -3
Bons estudos, dúvidas só chamar !!! :))
Vamos lá,
={(-2)²+[(-2)²-3+(-3).√49]:[√256:(-4)] }:(-3)
={ 4+[ 4-3+(-3).7]:[16:-4] }:-3
={ 4+[ 4-3 -21]:[-4] }:-3
={ 4+[ 1 -21]: -4 }:-3
={ 4+[ -20]: -4 }:-3
={ 4 -20: -4 }:-3
={ 4 + 5 }:-3
= 9 : -3
= -3
Bons estudos, dúvidas só chamar !!! :))
Perguntas similares
9 anos atrás
9 anos atrás
9 anos atrás